2008
DOI: 10.1001/archdermatol.2008.518
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Safety of Dapsone Gel, 5%, for Topical Treatment of Acne Vulgaris

Abstract: To evaluate the risk of hemolysis in subjects with glucose-6-phosphate dehydrogenase (G6PD) deficiency who were treated for acne vulgaris with either dapsone gel, 5% (dapsone gel), or vehicle gel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 14 publications
0
33
0
1
Order By: Relevance
“…92,93 The safety of 5% dapsone gel applied twice daily has been demonstrated in patients who are glucose 6 phosphate dehydrogenase-deficient and in patients who are sulfonamide allergic. [94][95][96] The most common applicationsite reactions consisted of erythema and dryness that were similar between groups. A temporary orange staining of the skin can occur when BP and topical dapsone are used together.…”
Section: Topical Dapsonementioning
confidence: 99%
“…92,93 The safety of 5% dapsone gel applied twice daily has been demonstrated in patients who are glucose 6 phosphate dehydrogenase-deficient and in patients who are sulfonamide allergic. [94][95][96] The most common applicationsite reactions consisted of erythema and dryness that were similar between groups. A temporary orange staining of the skin can occur when BP and topical dapsone are used together.…”
Section: Topical Dapsonementioning
confidence: 99%
“…S8), suggesting that DDS is not life-threatening in humans. Recently, a 5% DDS gel, which achieves a plasma concentration of about 20 Ī¼M, was reported to be safe and effective for longterm treatment (31). If DDS is to be used in a safer way, the treatment of DDS at a lower concentration may be more beneficial.…”
mentioning
confidence: 99%
“…Clinical studies have shown that dapsone gel 5% was effective in the treatment of acne vulgaris [5] with approximately 1% of the systemic exposure that is seen with typical oral dapsone treatment [13,14]. After treatment with dapsone gel 5%, no clinical or laboratory evidence of drug induced hemolytic anaemia was noted in G6PD deficient subjects with acne vulgaris [15].…”
Section: Resultsmentioning
confidence: 99%